2021
DOI: 10.1523/jneurosci.1232-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Visual Motion and Decision-Making in Dyslexia: Reduced Accumulation of Sensory Evidence and Related Neural Dynamics

Abstract: Children with and without dyslexia differ in their behavioural responses to visual information, particularly when required to pool dynamic signals over space and time. Importantly, multiple processes contribute to behavioural responses. Here we investigated which processing stages are affected in children with dyslexia when performing visual motion processing tasks, by combining two methods that are sensitive to the dynamic processes leading to responses. We used a diffusion model which decomposes response tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 104 publications
1
22
0
Order By: Relevance
“…[ 36 , 41 ]) and previous studies of motion processing in dyslexia (e.g. [ 8 ]) have also relied purely on accuracy indices, group differences between dyslexic children and typically developing children have recently been shown in drift-diffusion model studies, which model both accuracy and response time data [ 52 , 69 ]. These studies have shown that dyslexic children accumulate evidence from motion displays more slowly than typically developing children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 36 , 41 ]) and previous studies of motion processing in dyslexia (e.g. [ 8 ]) have also relied purely on accuracy indices, group differences between dyslexic children and typically developing children have recently been shown in drift-diffusion model studies, which model both accuracy and response time data [ 52 , 69 ]. These studies have shown that dyslexic children accumulate evidence from motion displays more slowly than typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of differences found here for dyslexic children compared to typically developing children (increased internal noise in the motion task and elevated orientation-coherence thresholds) is therefore different to that reported for autistic children. Therefore, we suggest that perceptual differences are specific to each condition (see also [ 52 , 71 ]. Accounts which suggest general impairments in motion processing across neurodevelopmental disorders (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech recognition is an effortful task for people with dyslexia, thus integrating an acoustic signal with language while performing another task can be extremely challeniging (Derawi et al, 2022). Individuals with dyslexia also have a reduced sensitivity to visual information over space and time (Manning et al, 2022).…”
Section: Sensory Processing and Neurodivergencementioning
confidence: 99%
“…Such differences in decision-making may influence an individual’s ability to learn from phonological information for a variety of reasons, e.g., limiting the individual’s ability to properly build expected outcomes, accumulate enough information for a decision, determine probabilistic contingencies, rank competing choices, place value on the outcome after a decision, etc. Indeed, two recent studies found inefficient evidence accumulation in dyslexia ( Stefanac et al, 2021 ; Manning et al, 2022 ); however, to our knowledge, other components of decision-making in dyslexia have yet to be explored.…”
Section: Introductionmentioning
confidence: 97%